Perbandingan Implementasi Kebijakan Pariwisata Halal Di Indonesia Dan Jepang - Nabila, Fitri; Dompak, Timbul; Khairina, Etika (LPPM Universitas Putera Batam, 2024)
Halal tourism is a rapidly growing segment of the tourism industry with significant economic potential. Both Indonesia and Japan have sizeable Muslim populations and have shown their commitment in developing halal tourism. In the Global Muslim Travel Index (GMTI) Indonesia won the title of Top Muslim Friendly Destination of the Year 2023 while Japan is ranked 6th in the Global Muslim Friendly Destination category for Non-OIC countries. The method used in this research is qualitative research method with comparative study. The purpose of this study is to compare the implementation of halal tourism policies in Indonesia and Japan